Intellectual Property : A Power Tool For Economic Growth - Idris, Kamil
This book is designed to be a practical guide to the use of intellectual property as a "power tool" for economic growth and wealth creation. Its aim is to give the interested non-specialist an understanding of how intellectual property, such as patents, trademarks and copyright have become increasingly valuable assets that can be used in many creative ways to increase material, social, and cultural well-being. It tells the story of how the information technology revolution, and the increasing pace, impact and importance of invention and innovation linked to rapid globalization have brought intellectual property into the limelight, making it a key element in government policy-making and corporate strategic planning. Read less
Keywords: Economic development; Intellectual property; Intellectual property -- Economic aspects